The Effect of Animated Health Education Videos on Knowledge of Premarital Sexual Health: A Quasi Experimental Study - Nengsih, Novida; Simanjuntak, Masrina Naomi Wulantari; Listautin, Listautin (Yayasan Ahmad Mansyur Nasirah, 2025)
Adolescence is a developmental period characterized by increased vulnerability to risky behaviors, including premarital sexual behavior. Inadequate sexual health knowledge among adolescents may lead to unintended pregnancies, increased maternal health risks such as anemia and pregnancy-related bleeding, and adverse psychological consequences, all of which can negatively affect adolescents’ future well-being. Therefore, effective sexual health education is essential to improve adolescents’ knowledge and prevent risky sexual behavior. This study aimed to examine the effect of health education delivered through animated videos on adolescents’ knowledge of premarital sexual health. This study employed a quasi-experimental one-group pretest–posttest design. The research was conducted at a vocational high school in Jambi City in June 2025. A total of 117 students were selected using purposive sampling. Adolescents’ knowledge of premarital sexual health was measured before and after the intervention. Data were analyzed using the Wilcoxon signed-rank test. The results shows that the mean knowledge score increased from 7.43 before the intervention to 9.14 after the intervention. The minimum score increased from 4 to 5, while the maximum score increased from 10 to 11. Statistical analysis showed a significant improvement in knowledge after the health education intervention using animated videos (p = 0.000, p < 0.05). In conclusion, health education using animated video media significantly improves adolescents’ knowledge of premarital sexual health. Animated videos can be considered an effective educational tool for adolescent sexual health promotion.